IBM FlashSystem Best Practices and Performance Guidelines - Nayak, Anil; Rainero, Antonio; Whyte, Barry; Hoffmann, Chris; Miyasiro, Danilo; Green, David; Bolland, Duane; Shea, Jackson; Herd, Jon; Fincher, Jordan; Avalos, Marcelo; Kubin, Sergey; et al. (IBM Redbooks, 2021)
This IBM® Redbooks® publication captures several of the preferred practices and describes the performance gains that can be achieved by implementing the IBM FlashSystem products. These practices are based on field experience. This book highlights configuration guidelines and preferred practices for the storage area network (SAN) topology, clustered system, back-end storage, storage pools and managed disks, volumes, remote copy services, and hosts. It explains how you can optimize disk performance with the IBM System Storage® Easy Tier® function. It also provides preferred practices for monitoring, maintaining, and troubleshooting. This book is intended for experienced storage, SAN, IBM FlashSystem, SAN Volume Controller (SVC), and IBM Storwize® administrators and technicians. Understanding this book requires advanced knowledge of these environments.